2018
DOI: 10.1158/1538-7445.sabcs17-gs6-02
|View full text |Cite
|
Sign up to set email alerts
|

Abstract GS6-02: The benefit of abemaciclib in prognostic subgroups: An exploratory analysis of combined data from the MONARCH 2 and 3 studies

Abstract: Background: Abemaciclib is an orally administered, selective inhibitor of cyclin-dependent kinases 4 & 6 that is dosed on a twice daily continuous schedule. Abemaciclib has demonstrated clinical efficacy with a generally tolerable safety profile in patients with hormone receptor-positive (HR+), human epidermal growth factor receptor 2-negative (HER2-) advanced breast cancer in combination with fulvestrant in MONARCH 2 (NCT02107703) and in combination with non-steroidal aromatase inhibitors (NSAI) in MONARC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 0 publications
0
17
0
2
Order By: Relevance
“…A combined analysis of MONARCH-2 and MONARCH-3 presented at the San Antonio Breast Cancer Symposium in 2017 found that patients with progression after more than 3 years after adjuvant endocrine therapy completion and patients with bone-only metastatic disease might receive only a modest benefit of abemaciclib plus ET versus ET-alone. 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…A combined analysis of MONARCH-2 and MONARCH-3 presented at the San Antonio Breast Cancer Symposium in 2017 found that patients with progression after more than 3 years after adjuvant endocrine therapy completion and patients with bone-only metastatic disease might receive only a modest benefit of abemaciclib plus ET versus ET-alone. 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…The impact of clinical factors as predictors of responsiveness to abemaciclib was investigated by a combined analysis of MONARCH-2 and MONARCH-3 studies including over 1000 patients 83 . This analysis confirmed the following factors to have a prognostic value: liver metastases, boneonly disease, tumor grade, progesterone receptor (PR) expression, and ECOG performance status.…”
Section: Clinical Parametersmentioning
confidence: 99%
“…The analysis showed that subgroups of patients who had a poor prognosis benefited the most from abemaciclib, and such an improvement was characterized by an improvement of mPFS (HR: 0.4 to 0.5) and ORR (more than 30%). Therefore, such clinical factors are an indicator that may help to guide clinicians to add abemaciclib to endocrine therapy 83 .…”
Section: Clinical Parametersmentioning
confidence: 99%
“…Unfortunately, it has not been possible to identify subsets who will not benefit from the addition of CDK4/6 inhibitors, as reported from an analysis of MONARCH 3 (Figure 1). 16 "Benefit was seen in all subsets, but what was interesting was that the worse the prognosis, based on clinical features, the bigger the gain from the addition of the CDK4/6 inhibitor," he noted. "This may suggest there is a group who are particularly likely to benefit.…”
Section: Cdk4/6 Inhibitors Are Game-changersmentioning
confidence: 99%